Building systemic resilience in school systems the way forward. (Asian Development Bank, 2020)
The sudden shift to online learning due to COVID-19 has worsened education sector inequalities. Blended learning along with adequate resources can help avoid the digital divide. The recommendations in this brief were gathered from an online workshop in October 2020 that was organized by ADB and The HEAD Foundation. The workshop involved policymakers, teacher educators, and school leaders from Bangladesh, Cambodia, the Lao People Democratic Republic, the Kyrgyz Republic, and VietNam.